Arabska Wiosna w Syrii. Implikacje dla polityki regionalnej Turcji - Smoleń, Kinga (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2014)
Wybuch Arabskiej Wiosny w Syrii spowodował przewartościowanie polityki regionalnej Turcji. Stanęła ona przed wyborem. Czy promować w Syrii i w całym regionie Bliskiego Wschodu zasady demokracji i reagować na przypadki łamania praw człowieka, wskazując tym samym kierunek niezbędnych przemian. Czy nawiązując do zasady tzw. zero problemów z sąsiadami kontynuować pragmatyczną współpracę z reżimem. Zwyciężyła polityka ochrony demokracji i praw człowieka. Wybór ten, z jednej strony zacieśnia relacje Turcji ze strukturami zachodnimi. Z drugiej, naraża na otwarty konflikt z Syrią oraz pogorszenie relacji z Iranem, które mogą mieć negatywne konsekwencje dla jej bezpieczeństwa i powiązań gospodarczych z Bliskim Wschodem. Uwzględniając złożoną sytuację na Bliskim Wschodzie, przywódcy Republiki Turcji za optymalne uznają: utrzymanie integralności terytorialnej Syrii; zapobieżenie wybuchowi konfliktu wyznaniowego, który może rozprzestrzenić się na obszar całego Bliskiego Wschodu oraz stopniową demokratyzację ogarniętego walkami państwa. Jednocześnie nie wykluczają oni bezpośredniego zaangażowania w konflikt w trzech przypadkach. Po pierwsze, przystąpienia do interwencji zbrojnej członków Sojuszu Północnoatlantyckiego. Po drugie, konieczności ochrony własnej ludności i terytorium. Po trzecie, eskalacji walk, bądź ich przeniesienia poza granice Syrii.

The events of the Arab Spring in Syria have led to the re-evaluation of the regional policy of the Republic of Turkey, which has faced two options. One involves acting in compliance with the expectations of its Western allies, and promoting the principles of democracy in the Middle East by firmly reacting against any cases of human rights’ violations, simultaneously showing the direction of the changes necessary in the region. Another refers to the principles included in the definition of the international policy of „Strategic Depth”: avoiding problems with neighbors, which excludes all interference in the internal politics of other countries, and means the continuation of pragmatic co-operation with all political centers, including authoritarian regimes. In the face of the violent struggle between the opposition and Al-Assad supporters, a policy of the protection of democracy and human rights has been chosen. This decision, on the one hand, strengthens Turkey’s relations with Western structures. On the other hand, it may lead to open conflict with a direct neighbor, Syria, which constitutes a serious threat to Turkey’s security, and may result in negative consequences for its energy security and economic relations with its Middle East partners. The Republic of Turkey does not exclude direct engagement in a potential military intervention in three cases. Firstly, if Turkey’s NATO allies decide to start military operations in Syria. Secondly, should it become necessary to protect its people and its territory. Thirdly, in the case of the conflict’s escalation or its spread outside Syria’s borders.
The Arab Spring in Syria and its Implications for the Regional Policy of Turkey
Keywords: Turcja; Arabska Wiosna; Syria; polityka regionalna; Turkey; Arab Spring; Syria; regional policy